Preparation method of porous silicon carbon, porous silicon carbon, composite pole piece and secondary battery

By establishing an index parameter model in the preparation process of porous silicon carbon, the problem of time-consuming and labor-intensive preparation of porous carbon materials in the existing technology is solved, and the rapid and accurate preparation of high-performance porous silicon carbon materials is achieved, which improves the performance and production of batteries. efficiency.

CN119461366APending Publication Date: 2025-02-18XIANTAO HAIRONG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411947378.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The lack of precise standards in the prior art to evaluate porous carbon models suitable for silicon-carbon composites, which makes the process of preparing porous carbon materials time-consuming and labor-intensive, and difficult to ensure product quality and production efficiency.

Method used

By establishing an index parameter model for carbonized and activated products, using the various index parameters of carbonized and activated products in the preparation of porous silicon carbon and guide the preparation and production of porous silicon carbon materials, reduce the test process, and improve product quality and production efficiency.

Benefits of technology

It realizes the rapid and precise preparation of porous silicon carbon materials with excellent performance, reduces the test process of silicon carbon deposition verification, and improves the expansion rate and circulation capacity retention rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461366A_ABST
    Figure CN119461366A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of porous silicon carbon, the porous silicon carbon, a composite pole piece and a secondary battery, in the preparation method of the porous silicon carbon, indexes of a carbonized product and an activated product meet the following relation: # imgabs0 #, D00, D100, D10, D50 and D90 are corresponding particle size values when cumulative distribution of particles of the carbonized product on a particle size distribution curve reaches 0.1%, 100%, 10%, 50% and 90% respectively; p1, P2 and P3 are the microporosity, the mesoporosity and the macroporosity of the activated product respectively; n is the average pore size of the activated product. By utilizing the method, relevant conditions and parameters of carbonization and activation can be properly adjusted, the porous silicon-carbon material with excellent performance can be rapidly prepared and has higher silicon-carbon first effect and silicon-carbon capacity, and a prepared battery is lower in expansion rate and higher in cycle capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to a method for preparing porous silicon carbon, porous silicon carbon, a composite pole piece and a secondary battery. Background Art

[0002] At present, the demand for electricity of various electric tools and equipment such as electric vehicles is growing, and people have put forward higher requirements for the energy density of lithium-ion batteries. The theoretical capacity of silicon materials is as high as 4200mAh / g, which is far higher than the widely used graphite negative electrode materials (the theoretical lithium storage capacity of graphite is only 372mAh / g). Therefore, in the selection of battery negative electrode materials, adding silicon-based materials has become a common solution. However, the volume of silicon negative electrode expands significantly during the charging and discharging process (the expansion rate is as high as 300%), which limits its potential in large-scale applications. Therefore, it is of great significance to research and commercialize the development of low-expansion silicon-based negative electrode materials.

[0003] In order to reduce the expansion rate of silicon anodes and solve the problem of excessive expansion rate of silicon anodes, a common practice is to deposit nano-silicon in porous carbon materials, and reduce the impact of silicon anode expansion by reserving gaps in the space inside the porous carbon. However, there is currently a lack of an accurate standard to evaluate porous carbon models suitable for silicon-carbon composites, which means that the prepared porous carbon must be actually used for silicon deposition before performance testing can be performed, which is both time-consuming and laborious. Summary of the invention

[0004] The present invention aims to solve the technical problems in the prior art, and discloses a method for preparing porous silicon carbon, porous silicon carbon, a composite pole piece and a secondary battery. The present invention uses the index parameters of the carbonized product and the activated product in the preparation process of porous silicon carbon to establish an index parameter model suitable for preparing porous silicon carbon materials. According to the model, the preparation and production of porous silicon carbon can be guided faster and more accurately, the test process can be reduced, and the product quality and production efficiency can be improved.

[0005] The present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for preparing porous silicon carbon, comprising the following steps:

[0007] (1) steam-activating the carbonized product to form an activated product;

[0008] (2) depositing silicon raw material into the porous structure of the activated product by vapor deposition to produce porous silicon carbon;

[0009] Among them, the indicators of carbonized products and activated products satisfy the following relationship:

[0010]

[0011] In the formula,

[0012]

[0013] in,

[0014] D00, D100, D10, D50, and D90 are the particle size values ​​corresponding to the cumulative distribution of carbonized particles on the particle size distribution curve when reaching 0.1%, 100%, 10%, 50%, and 90% respectively;

[0015] P1, P2, and P3 are the microporosity, mesoporosity, and macroporosity of the activated product, respectively;

[0016] N is the average pore size of the activated product.

[0017] Preferably, the M value is 19-30.

[0018] Furthermore, D10, D50, and D90 of the carbonized product satisfy the following relationship:

[0019]

[0020] Furthermore, the carbonized product has a D00 ≥ 2um and a D100 ≤ 25um.

[0021] Furthermore, the microporosity P1, mesoporosity P2, and macroporosity P3 of the activated product satisfy the following relationship:

[0022]

[0023] Preferably, m=2300-3500.

[0024] Furthermore, the average pore size of the activated product is N=1-2 nm.

[0025] Furthermore, the steam activation temperature is 700-900° C., and the activation time is 1-4 hours.

[0026] Preferably, water vapor is used for activation in a rotary kiln with a rotation speed of 10 to 40 Hz and a flow rate of 0.5 to 4 L / min.

[0027] Further, the raw material is carbonized to obtain a carbonized product;

[0028] Preferably, the raw material used for carbonization is a biomass raw material or a resin-based raw material;

[0029] Preferably, the biomass raw material is one or more of coconut shell, straw, rice husk, wood, bamboo, bagasse, nut shell, and animal bone marrow;

[0030] Preferably, the resin-based raw material is one or more of phenolic resin, epoxy resin, and urea-formaldehyde resin;

[0031] Preferably, the carbonization temperature is 600-1000°C and the carbonization time is 4-10h;

[0032] Preferably, the carbonizing gas is nitrogen;

[0033] Preferably, the vapor deposition method is specifically as follows: depositing the activated product and the silicon raw material in a mass ratio of (1-10): (1-2), heating to 400-600°C at a heating rate of 2-20°C / min, keeping the temperature for 1-4 hours, then heating to 450-650°C at a step temperature gradient of 1-5°C, keeping the temperature for 1-4 hours, during which the rotary kiln speed is maintained at 10-40 Hz, to obtain CVD-coated porous silicon carbon;

[0034] Preferably, the silicon raw material is one or more of silane, disilane, and dichlorosilane gases.

[0035] The present invention also provides porous silicon carbon produced by the method for producing porous silicon carbon.

[0036] The present invention also provides a composite pole piece, comprising the porous silicon carbon mentioned above, or comprising the porous silicon carbon made by the above method.

[0037] The present invention also provides a secondary battery, comprising the porous silicon carbon, or comprising the porous silicon carbon produced by the method.

[0038] The present invention has the following beneficial effects:

[0039] The present invention can be used to appropriately adjust the carbonization and activation related conditions and parameters, quickly prepare porous silicon-carbon materials with excellent performance, and make them have higher silicon-carbon first effect and silicon-carbon capacity, and the battery expansion rate is lower and the cycle capacity retention rate is higher. The present invention uses the various index parameters of the carbonized product and the activated product in the porous silicon-carbon preparation process to establish an index parameter model formula suitable for preparing porous silicon-carbon materials. According to the formula, the verification of silicon-carbon deposition after porous carbon production can be reduced, the test process can be reduced, and the preparation and production of porous carbon can be effectively guided. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0041] Figure 1 This is an electron microscope EDS scanning image of the porous silicon carbon prepared in Example 1 (Si element);

[0042] Figure 2 This is an electron microscope EDS scanning image of the porous silicon carbon prepared in Comparative Example 1 (Si element). DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. If the specific conditions are not specified in the embodiments, they shall be carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made by commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The disclosure of the numerical range involved includes all values ​​in the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given for these ranges.

[0044] The present invention provides a method for preparing porous silicon carbon, comprising the following steps:

[0045] (1) steam-activating the carbonized product to form an activated product;

[0046] (2) depositing silicon raw material into the porous structure of the activated product by vapor deposition to produce porous silicon carbon;

[0047] Among them, the indicators of carbonized products and activated products satisfy the following relationship:

[0048]

[0049] In the formula,

[0050]

[0051] in,

[0052] D00, D100, D10, D50, and D90 are the particle size values ​​corresponding to the cumulative distribution of carbonized particles on the particle size distribution curve when reaching 0.1%, 100%, 10%, 50%, and 90% respectively;

[0053] P1, P2, and P3 are the microporosity, mesoporosity, and macroporosity of the activated product, respectively;

[0054] N is the average pore size of the activated product.

[0055] Preferably, the M value is 19-30.

[0056] Preferably, the carbonized product is activated using water vapor.

[0057] The present invention fully considers various index parameters of carbonized products and activated products in the preparation process of porous silicon carbon, and analyzes in detail the influence of the correlation between various index parameters on the electrical properties of porous carbon materials, and establishes the above-mentioned index parameter model formula suitable for preparing porous silicon carbon materials.

[0058] In this formula, D00 / D100 reflects the influence of the particle size width of D00~D100 on the electrical properties of porous silicon-carbon materials; P reflects the influence of the particle size width of D10~D90 on the electrical properties of porous silicon-carbon materials; m reflects the influence of the ratio between microporosity, mesoporosity and macroporosity on the electrical properties of porous silicon-carbon materials; N reflects the influence of the average pore size on the electrical properties of porous silicon-carbon materials.

[0059] According to this formula, the particle size width of D00-D100 and D10-D90 in the carbonization process, as well as the microporosity, mesoporosity, macroporosity and average pore size in the activation process can be adjusted to meet the numerical range of M. When M=4-30, the porous carbon material can show excellent comprehensive electrical properties. Through this formula, the appropriate parameters and conditions for each stage in the production of porous carbon can be quickly obtained, which is suitable for the production of porous carbon with silicon deposition, and can reduce the verification of silicon carbon deposition after the production of porous carbon, reduce the test process, and guide the preparation and production of porous carbon.

[0060] In some embodiments, D00 of the carbonized product is ≥ 2 um and D100 is ≤ 25 um.

[0061] D00 and D100 together describe the size distribution range of porous carbon material particles. D00 provides a reference for the minimum size of the particles, while D100 provides a reference for the maximum size of the particles. These two parameters directly affect the pore characteristics and surface contact area of ​​the material, thereby affecting the electrical properties of the material.

[0062] If D00 is too small, it means that there are more small-sized particles in the material. During the activation process, these small particles will be more likely to have their skeletons crushed due to thermal stress or chemical action. This is because the surface area of ​​small particles is relatively large, making them more susceptible to erosion under high temperature or chemical activators. When the small particle skeleton is crushed during the activation process, more fine powder will be produced. These fine powders will block the pores and affect the pore structure and air permeability of the material, thereby reducing the material's adsorption of silicon raw materials. At the same time, the specific surface area increases, increasing the side reactions with the electrolyte, resulting in a low first efficiency of the battery. Therefore, if D00 is too small, it is easy to cause some small particle skeletons to be crushed during activation, and the fine powder increases, which reduces the material's adsorption of silicon raw materials, and at the same time, the first efficiency of the silicon-carbon finished product is reduced.

[0063] A larger D100 means that there are more macroporous structures in the porous carbon material, which will cause silicon crystallization during the silicon deposition process, resulting in final expansion and enlargement, and ultimately lead to a decrease in the stability of the structure during the cycle; in silicon-carbon composite materials, large-sized particles lead to stress concentration during the charge and discharge process, thereby increasing the risk of material rupture. This stress concentration will not only cause repeated cracking and fragmentation of silicon particles, but also cause continuous destruction and thickening of the solid electrolyte interface layer (SEI), rapidly consuming electrolyte and lithium ions; a larger D100 requires additional processing steps to reduce the particle size, which not only increases the difficulty of processing, but may also lead to increased costs. Therefore, a larger D100 will have an adverse effect on the processing performance of silicon-carbon finished products, increase processing difficulty, and affect structural integrity and electrochemical performance.

[0064] A larger D00 and a smaller D100 means a lower material yield and increased production costs.

[0065] The above factors will have a negative impact on the electrical properties of the porous carbon material. Therefore, when preparing the porous carbon material, the present invention reasonably controls the D00 and D100 values ​​to satisfy D00≥2um and D100≤25um, which is crucial for optimizing the electrical properties of the porous carbon material in the present invention.

[0066] At the same time, the difference between D00 and D100 also has a significant effect on the electrical properties of porous carbon materials. This difference reflects the width of the particle size distribution, that is, the uniformity of the particle size. A smaller difference between D00 and D100 means that the particle size distribution is more concentrated. This uniformity helps to improve the conductivity of the material, because the uniform particle size can reduce the contact resistance inside the material, making the electron transmission smoother; the size of the difference between D00 and D100 also affects the uniformity of the pore structure. A smaller difference means that the pore structure is more uniform, which helps to improve the adsorption efficiency of silicon raw materials, thereby improving electrochemical performance; a smaller difference between D00 and D100 means that there are more micropores or mesopores, which increases the specific surface area of ​​the material and provides more active sites for electrochemical reactions, thereby improving the adsorption efficiency of silicon raw materials.

[0067] In some embodiments, D10, D50, and D90 of the carbonized product satisfy the following relationship:

[0068]

[0069] D10 refers to the particle size value corresponding to the point where the cumulative distribution reaches 10% on the particle size distribution curve, that is, 10% of the particle diameters are less than or equal to this value. The smaller the D10 value, the higher the proportion of smaller particles in the material; D50 refers to the particle size value corresponding to the point where the cumulative distribution percentage reaches 50% on the particle size distribution curve. This parameter is also called the median particle size. D50 is an important indicator for measuring the center position of the particle size distribution and can well represent the average particle size of the particle group; D90 refers to the particle size value corresponding to the point where the cumulative distribution percentage reaches 90% on the particle size distribution curve, which means that in the particle group of porous carbon materials, 90% of the particles have a particle size smaller than the D90 value, and the remaining 10% of the particles have a particle size larger than the D90 value.

[0070] The P value reflects the average value of D10, D50, and D90. If the P value is too small, the yield will be low and the cost will increase; if the P value is too large, the particle size distribution will be wide, resulting in poor silane adsorption, poor deposition uniformity in the later stage, and large expansion of the silicon-carbon finished product. A relatively suitable particle size distribution is more conducive to the uniform distribution and adsorption of silane molecules. Therefore, the P value is controlled within the range of 6 to 10.

[0071] In some embodiments, after the activation process, a porous carbon skeleton, i.e., an activated product, is obtained, and the microporosity P1, mesoporosity P2, and macroporosity P3 are measured, satisfying the following relationship:

[0072]

[0073] Preferably, m=2300-3500.

[0074] In some embodiments, after the activation process, a porous carbon skeleton, ie, an activated product, is obtained with an average pore size N=1-2 nm.

[0075] In some embodiments, the steam activation temperature is 700-900° C., and the activation time is 1-4 hours.

[0076] Preferably, water vapor is used for activation in a rotary kiln with a rotation speed of 10 to 40 Hz and a flow rate of 0.5 to 4 L / min.

[0077] The microporosity P1 is the ratio of the volume of pores with a pore diameter of ≤2nm to the total pore volume. Micropores can increase the specific surface area of ​​the material and provide active sites. The microporosity affects the adsorption capacity and electrochemical performance of the material.

[0078] The mesoporosity P2 is the ratio of the volume of pores with a pore diameter between 2 nm and 50 nm to the total pore volume.

[0079] The macroporosity P3 is the ratio of the volume of pores with a pore diameter of ≥50 nm to the total pore volume.

[0080] Too high a mesoporosity P2 or a macroporosity P3 will lead to silicon crystallization during silicon deposition, increase expansion, and cause silicon pulverization in the later stage, thereby deteriorating the cycle.

[0081] In the formula, if the m value is too large, the pore volume is too low, resulting in a low capacity of the porous silicon carbon; if the m value is too small, the expansion rate of the porous silicon carbon will be too large. Therefore, the appropriate range of the m value is 800 to 4000, preferably 2300 to 3500.

[0082] In the formula, if the N value is too small, the pore volume is too low, and the capacity of the porous silicon carbon is too low; if the N value is too large, the expansion rate of the porous silicon carbon is large. Therefore, the appropriate range of N value is 1 to 2nm.

[0083] P1, P2, P3, i.e., m value, and N value in the formula are affected by temperature, time, rotation speed and flow rate during the activation process.

[0084] Too low activation temperature, too low activation time, too low rotation speed, and too low flow rate may even lead to P2=P3=0%, m value>4000 or even approaching infinity, resulting in too low pore volume and too low capacity of porous silicon-carbon materials; relatively low activation temperature, relatively short activation time, relatively low rotation speed, and relatively low flow rate may easily lead to insufficient activation, failure to fully form a pore structure that is conducive to the adsorption of silicon raw materials, low pore volume, and low capacity of porous silicon-carbon.

[0085] If the activation temperature is too high, the activation time is too high, the rotation speed is too high, and the flow rate is too high, the microporous structure will be destroyed or merged into larger pores during the activation process, and the microporosity will decrease, which will make P1 too low and P2 and P3 too high, resulting in m < 800, which will increase the expansion rate of porous silicon carbon. Relatively high activation temperature, relatively long activation time, relatively high rotation speed, and relatively high flow rate will increase the original pore structure inside the carbon material, resulting in N>2nm, which will increase the expansion rate of porous silicon carbon.

[0086] In addition, the particle size distribution during the carbonization process will also affect the values ​​of P1, P2, P3, and N. If the particle size of D00-D100 is too wide, the microporosity P1 will be reduced, making P1 low, resulting in m<800, and N>2nm; if the particle size of D10-D90 is too wide, P1 will be low, m<800, and N>2nm; if the particle size of D00-D100 is too narrow, the yield will be low and the cost will be high.

[0087] In summary, the values ​​of P1, P2, P3, m, and N can be adjusted by controlling the temperature, time, rotation speed, and flow rate during the activation process, as well as the particle size distribution during the carbonization process. Thus, the m value is within the appropriate range of 800 to 4000, preferably within the range of 2300 to 3500, and the N value is within the range of 1 to 2 nm, so as to improve the performance of the porous silicon-carbon material.

[0088] Furthermore, the carbonized product can be purchased directly or obtained through preparation;

[0089] Preferably, the carbonized product is obtained by carbonizing the raw material;

[0090] Preferably, the raw material used for carbonization is a biomass raw material or a resin-based raw material;

[0091] Preferably, the biomass raw material is one or more of coconut shell, straw, rice husk, wood, bamboo, bagasse, nut shell, and animal bone marrow;

[0092] Preferably, the resin-based raw material is one or more of phenolic resin, epoxy resin, and urea-formaldehyde resin;

[0093] Preferably, the vapor deposition method is specifically as follows: depositing the activated product and the silicon raw material in a mass ratio of (1-10): (1-2), heating to 400-600°C at a heating rate of 2-20°C / min, keeping the temperature for 1-4 hours, then heating to 450-650°C at a step temperature gradient of 1-5°C, keeping the temperature for 1-4 hours, during which the rotary kiln speed is maintained at 10-40 Hz, to obtain CVD-coated porous silicon carbon;

[0094] Preferably, the silicon raw material is one or more of silane, disilane, and dichlorosilane gases.

[0095] The present invention can be used to appropriately adjust the carbonization and activation related conditions and parameters, quickly prepare porous silicon-carbon materials with excellent performance, and make them have higher silicon-carbon first effect and silicon-carbon capacity, and the expansion rate of the manufactured battery is lower, and the cycle capacity retention rate is higher. The present invention uses the index parameters of the carbonized product and the activated product in the porous silicon-carbon preparation process to establish an index parameter model formula suitable for preparing porous silicon-carbon materials. According to the formula, the verification of silicon-carbon deposition after porous carbon production can be reduced, the test process can be reduced, and the preparation and production of porous carbon can be effectively guided.

[0096] The present invention also provides porous silicon carbon produced by the method for producing porous silicon carbon.

[0097] The present invention also provides a composite pole piece, comprising the porous silicon carbon mentioned above, or comprising the porous silicon carbon made by the above method.

[0098] The present invention also provides a secondary battery, comprising the porous silicon carbon, or comprising the porous silicon carbon produced by the method.

[0099] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.

[0100] In each embodiment and comparative example of the present invention, the testing method of microporosity, mesoporosity, macroporosity and average pore size is as follows: a physical adsorption instrument (model: BK200C) is used to test the microporosity, mesoporosity, macroporosity and average pore size in the present invention by static capacity adsorption method. The specific testing method refers to the national standard SY / T 6154-2019.

[0101] In each embodiment and comparative example of the present invention, the prepared porous silicon-carbon material is used to make a negative electrode composite pole piece. The specific method is: the silicon-carbon material is mixed with graphite, CMC (sodium carboxymethyl cellulose), SBR (styrene-butadiene rubber), and PAA (polyacrylic acid) in a mass ratio of 20:76:1:1:2 to make a negative electrode pole piece, which is used to test two silicon-carbon performance indicators: silicon-carbon capacity and silicon-carbon first effect.

[0102] In each embodiment and comparative example of the present invention, a secondary battery is made by using a negative electrode sheet, specifically, the negative electrode sheet is matched with an NCM (nickel cobalt manganese oxide) positive electrode to make a battery, and the battery is charged and discharged at 0.33C / 0.33C to measure the expansion rate after 500 cycles and the capacity retention rate after 500 cycles. Among them:

[0103]

[0104] Example 1

[0105] (1) Carbonization: Select the biomass raw material bamboo, crush, grind, shape, grade and carbonize, and obtain the carbonized product D00 = 2.5um, D100 = 24.1um, D10 = 4.0um, D50 = 7.3um, D90 = 14.2um, P = (D10 + D50 + D90) / 3 = 8.5;

[0106] (2) Activation: The treated carbonized product was activated by steam in a rotary kiln at an activation temperature of 800°C, an activation time of 3 h, a rotation speed of 30 Hz, and a flow rate of 2 L / min to obtain a porous carbon skeleton with a microporosity of P1 = 95%, a mesoporosity of P2 = 4%, a macroporosity of P3 = 1%, m = P1 / (P2*P3) = 2375, and an average pore size of N = 1.5 nm;

[0107] In this embodiment, the parameter indexes of the carbonized product and the activated product are in accordance with the following relationship:

[0108]

[0109] It can be obtained that M=19.3.

[0110] (3) Preparation of porous silicon carbon: The activated product and silane were deposited in a mass ratio of 50:50, heated to 500°C at a heating rate of 5°C / min, kept warm for 2 h, and then heated to 550°C with a step temperature gradient of 2°C, kept warm for 2 h, during which the rotary kiln speed was maintained at 30 Hz to obtain CVD-coated porous silicon carbon.

[0111] The porous silicon-carbon material obtained in this embodiment was made into a negative electrode plate, and the silicon-carbon performance indicators were tested: the silicon-carbon capacity was 2012 mAh / g, and the silicon-carbon first efficiency was 94.1%.

[0112] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 88%; the capacity retention rate after 500 cycles was 93%.

[0113] Example 2

[0114] The preparation method of this embodiment is different from that of Embodiment 1 in that D00 of the carbonized product is 2.1 um, D100 is 24.9 um; the microporosity P1 of the activated product is 94.1%, the mesoporosity P2 is 4.2%, the macroporosity P3 is 1.7%, m is P1 / (P2*P3) is 1317.9, and the average pore size N is 1.7 nm; M is 7.7.

[0115] The porous silicon-carbon material obtained in this embodiment is made into a negative electrode plate, and the silicon-carbon performance indicators are tested: the silicon-carbon capacity is 1978 mAh / g, and the silicon-carbon first efficiency is 93.7%.

[0116] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 93%; the capacity retention rate after 500 cycles was 91.5%.

[0117] Embodiment 3:

[0118] The preparation method of this embodiment is different from that of Embodiment 1 in that the carbonized product has D10=3.6um, D50=7.5um, D90=15um, and P=(D10+D50+D90) / 3=8.7; the activated product has a microporosity of P1=94.2%, a mesoporosity of P2=4.1%, and a macroporosity of P3=1.7%, m=P1 / (P2*P3)=1351.5, and an average pore size of N=1.7nm; M=9.5.

[0119] The porous silicon-carbon material obtained in this embodiment is made into a negative electrode plate, and the silicon-carbon performance indicators are tested: the silicon-carbon capacity is 1988 mAh / g, and the silicon-carbon first efficiency is 93.9%.

[0120] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 92.7%; the capacity retention rate after 500 cycles was 91.6%.

[0121] Embodiment 4:

[0122] The preparation method of this embodiment is different from that of Embodiment 1 in that D00 of the carbonized product is 3 um, D100 is 23 um; the microporosity P1 of the activated product is 95.2%, the mesoporosity P2 is 3.8%, the macroporosity P3 is 1.0%, m is P1 / (P2*P3) is 2505.3, and the average pore size N is 1.4 nm; M is 27.5.

[0123] The porous silicon-carbon material obtained in this embodiment is made into a negative electrode plate, and the silicon-carbon performance indicators are tested: the silicon-carbon capacity is 2018 mAh / g, and the silicon-carbon first efficiency is 94.2%.

[0124] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 86%; the capacity retention rate after 500 cycles was 93.2%.

[0125] Embodiment 5:

[0126] The preparation method of this embodiment is different from that of Embodiment 1 in that the carbonized product has D10=4.2um, D50=7.1um, D90=13.5um, and P=(D10+D50+D90) / 3=8.3; the activated product has a microporosity of P1=95.3%, a mesoporosity of P2=3.9%, and a macroporosity of P3=0.8%, m=P1 / (P2*P3)=3054.5, and an average pore size of N=1.3nm; M=29.5.

[0127] The porous silicon-carbon material obtained in this embodiment was made into a negative electrode plate, and the silicon-carbon performance indicators were tested: the silicon-carbon capacity was 2022 mAh / g, and the silicon-carbon first efficiency was 94.3%.

[0128] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 85%; the capacity retention rate after 500 cycles was 93.3%.

[0129] Embodiment 6:

[0130] The difference between the preparation method of this embodiment and that of Embodiment 1 is that in the activation step, the activation temperature is 900°C and the activation time is 4h; the activated product has a microporosity P1=93.8%, a mesoporosity P2=4.5%, a macroporosity P3=1.7%, m=P1 / (P2*P3)=1226.1, an average pore size N=1.9nm; M=7.9.

[0131] The porous silicon-carbon material obtained in this embodiment was made into a negative electrode plate, and the silicon-carbon performance indicators were tested: the silicon-carbon capacity was 2035.6 mAh / g, and the silicon-carbon first efficiency was 93.6%.

[0132] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 95%; the capacity retention rate after 500 cycles was 91.1%.

[0133] Embodiment 7:

[0134] The difference between the preparation method of this embodiment and that of Embodiment 1 is that in the activation step, the rotation speed is 40 Hz and the flow rate is 4 L / min; the activated product has a microporosity P1=93.6%, a mesoporosity P2=4.7%, a macroporosity P3=1.7%, m=P1 / (P2*P3)=1171.5, and an average pore size N=2 nm; M=7.1.

[0135] The porous silicon-carbon material obtained in this embodiment is made into a negative electrode plate, and the silicon-carbon performance indicators are tested: the silicon-carbon capacity is 2033 mAh / g, and the silicon-carbon first efficiency is 93.3%.

[0136] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 96%; the capacity retention rate after 500 cycles was 91%.

[0137] Comparative Example 1:

[0138] The difference between the preparation method of this comparative example and Example 1 is that the carbonized product has D00=1.2um, D100=28um, D10=3um, D50=7.2um, D90=20um, P=(D10+D50+D90) / 3=10.1; the activated product has a microporosity P1=90%, a mesoporosity P2=8%, a macroporosity P3=2%, m=P1 / (P2*P3)=562.5, and an average pore size N=2.5nm; M=1.

[0139] The porous silicon-carbon material obtained in this comparative example was made into a negative electrode plate, and the silicon-carbon performance indicators were tested: the silicon-carbon capacity was 1768 mAh / g, and the silicon-carbon first efficiency was 91%.

[0140] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 110%; the capacity retention rate after 500 cycles was 85%.

[0141] Comparative Example 2:

[0142] The difference between the preparation method of this comparative example and Example 1 is that in the activation step, the activation temperature is 1000°C, the activation time is 5h, the rotation speed is 60Hz, and the flow rate is 6L / min; the microporosity P1 of the activated product is 82%, the mesoporosity P2 is 10%, the macroporosity P3 is 8%, m is P1 / (P2*P3) is 102.5, and the average pore size N is 3.5nm; M is 0.4.

[0143] The porous silicon-carbon material obtained in this comparative example was made into a negative electrode plate, and the silicon-carbon performance indicators were tested: the silicon-carbon capacity was 1750 mAh / g, and the silicon-carbon first efficiency was 90.8%.

[0144] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 130%; the capacity retention rate after 500 cycles was 81%.

[0145] Comparative Example 3:

[0146] The difference between the preparation method of this comparative example and that of Example 1 is that in the activation step, the activation temperature is 600°C, the activation time is 0.5h, the rotation speed is 5Hz, and the flow rate is 0.2L / min; the microporosity P1 of the activated product is 99%, the mesoporosity P2 is 0.8%, the macroporosity P3 is 0.2%, m is P1 / (P2*P3) is 61875, and the average pore size N is 0.8nm; M is 943.9.

[0147] The porous silicon-carbon material obtained in this comparative example was made into a negative electrode plate, and the silicon-carbon performance indicators were tested: the silicon-carbon capacity was 1400 mAh / g, and the silicon-carbon first efficiency was 89%.

[0148] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 140%; the capacity retention rate after 500 cycles was 75%.

[0149] Comparative Example 4:

[0150] The difference between the preparation method of this comparative example and Example 1 is that in the activation step, the activation temperature is 700°C and the activation time is 1h; the activated product has a microporosity P1=97%, a mesoporosity P2=2.5%, a macroporosity P3=0.5%, m=P1 / (P2*P3)=7760, an average pore size N=1.2nm; M=78.9.

[0151] The porous silicon-carbon material obtained in this comparative example was made into a negative electrode plate, and the silicon-carbon performance indicators were tested: the silicon-carbon capacity was 1879 mAh / g, and the silicon-carbon first efficiency was 92.1%.

[0152] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 84%; the capacity retention rate after 500 cycles was 93.2%.

[0153] Comparative Example 5:

[0154] The difference between the preparation method of this comparative example and Example 1 is that in the activation step, the rotation speed is 10 Hz and the flow rate is 0.5 L / min; the activated product has a microporosity P1=97.1%, a mesoporosity P2=2.4%, a macroporosity P3=0.5%, m=P1 / (P2*P3)=8091.7, and an average pore size N=1.3 nm; M=76.

[0155] The porous silicon-carbon material obtained in this comparative example was made into a negative electrode plate, and the silicon-carbon performance indicators were tested: the silicon-carbon capacity was 1860 mAh / g, and the silicon-carbon first efficiency was 92%.

[0156] The negative electrode sheet was made into a battery, and the battery performance indicators were tested: the expansion rate after 500 cycles was 83%; the capacity retention rate after 500 cycles was 93.3%.

[0157] The relevant conditions and parameters in Examples 1 to 7 and Comparative Examples 1 to 5 are shown in Tables 1, 2 and 3. Table 1 shows the main parameter indicators of the carbonized product during the preparation of the porous silicon-carbon material, Table 2 shows the main parameter indicators in the activation step, and Table 3 shows the main performance parameter indicators of the porous silicon-carbon material and the battery.

[0158] Table 1

[0159] Examples and Comparative Examples D00 / um D100 / um D10 / um D50 / um D90 / um P Example 1 2.5 24.1 4.0 7.3 14.2 8.5 Example 2 2.1 24.9 4.0 7.3 14.2 8.5 Example 3 2.5 24.1 3.6 7.5 15.0 8.7 Example 4 3.0 23.0 4.0 7.3 14.2 8.5 Example 5 2.5 24.1 4.2 7.1 13.5 8.3 Example 6 2.5 24.1 4.0 7.3 14.2 8.5 Example 7 2.5 24.1 4.0 7.3 14.2 8.5 Comparative Example 1 1.2 28.0 3.0 7.2 20.0 10.1 Comparative Example 2 2.5 24.1 4.0 7.3 14.2 8.5 Comparative Example 3 2.5 24.1 4.0 7.3 14.2 8.5 Comparative Example 4 2.5 24.1 4.0 7.3 14.2 8.5 Comparative Example 5 2.5 24.1 4.0 7.3 14.2 8.5

[0160] Table 2

[0161]

[0162] Table 3

[0163]

[0164]

[0165] It can be seen from the above embodiments and comparative examples that the M value calculated by the formula relationship of the present invention has a good correlation with the comprehensive electrical properties of the porous silicon-carbon material. Through the preparation method of the porous silicon-carbon material of the present invention, the various conditions and parameters in the carbonization process and the activation process are selected and controlled, and the various relevant conditions and parameters are adjusted according to the formula model in the present invention so that the M value is within the range of 4 to 30, which can comprehensively improve the comprehensive electrical properties of the porous silicon-carbon material such as silicon-carbon capacity, silicon-carbon first effect, expansion rate, and cycle capacity retention rate. As shown in Examples 1 to 7 relative to Comparative Examples 1 to 5, if the M value exceeds the above range, it will lead to a decrease in the comprehensive electrical properties of the porous silicon-carbon material. And, further, as shown in Examples 1, 4, and 5, relative to Examples 2, 3, 6, and 7, the M value is better in the range of 19 to 30. Figure 1The electron microscope EDS scanning image (Si element) of the porous silicon carbon prepared in Example 1 is shown. The green represents the deposited silicon area. Figure 2 Compared with the porous silicon carbon electron microscope EDS scanning image (Si element) prepared in Comparative Example 1, the deposition is more uniform, the expansion rate is lower, and the comprehensive electrical performance is better.

[0166] It can be seen from the above embodiments and comparative examples that the m value calculated by the formula of the present invention has a good correlation with the capacity and expansion rate of porous silicon carbon. Through the formula model in the present invention, the values ​​of P1, P2, and P3 are controlled by regulating the temperature, time, rotation speed, and flow rate during the activation process, or the particle size distribution during the carbonization process, that is, the m value is regulated in the range of 800 to 4000, so that the silicon carbon capacity and expansion rate of the prepared porous silicon carbon material can be relatively excellent. As shown in Examples 1 to 7 relative to Comparative Examples 1 to 5, if the m value exceeds the above range, it will result in too low silicon carbon capacity or too high expansion rate. And, further, as shown in Examples 1, 4, and 5 relative to Examples 2, 3, 6, and 7, the m value is better in the range of 2300 to 3500.

[0167] It can be seen from Example 1 and Comparative Example 1 that the particle size of D00-D100 is too wide, and the P value is too large, that is, the particle size of D10-D90 is too wide, exceeding the appropriate range of P=6-10, which will lead to a decrease in the microporosity P1 and make P1 too low, thus resulting in m<800, and also resulting in N>2nm, thereby reducing the comprehensive performance of porous silicon carbon.

[0168] By comparing Example 1 with Examples 2 and 3, it can be seen that when the particle size of D00-D100 becomes wider, or when the particle size of D10-D90 becomes wider, the microporosity P1 will decrease and the N value will increase. By comparing Example 1 with Examples 4 and 5, it can be seen that when the particle size of D00-D100 becomes narrower, or when the particle size of D10-D90 becomes narrower, the microporosity P1 will increase and the N value will decrease. Therefore, the values ​​of P1, P2, P3, m, and N can be regulated by adjusting the particle size distribution parameters during the carbonization process. Thereby, the m value is within the appropriate range of 800-4000, preferably m is within the range of 2300-3500, and the N value is within the range of 1-2nm, so as to improve the performance of the porous silicon-carbon material.

[0169] By comparing Example 1 with Comparative Example 2, it can be seen that if the activation temperature is too high, the activation time is too high, the rotation speed is too high, and the flow rate is too large, the microporous structure will be destroyed or merged into larger pores during the activation process, and the microporosity will decrease, which will make P1 too low, and P2 and P3 too high, resulting in m < 800, and the expansion rate of porous silicon carbon is too large; too high activation temperature, too long activation time, too high rotation speed, and too large flow rate will excessively increase the original pore structure inside the carbon material, resulting in N>2nm, and the expansion rate of porous silicon carbon is too large. By comparing Example 1 with Example 6, it can be seen that if the activation temperature and activation time are too high, the microporosity will be low, the N value will be high, and the expansion rate will be high. By comparing Example 1 with Example 7, it can be seen that if the rotation speed and flow rate are too high during the activation process, the microporosity will be low, the N value will be high, and the expansion rate will be high.

[0170] From the comparison between Example 1 and Comparative Example 3, it can be seen that if the activation temperature is too low, the activation time is too low, the rotation speed is too low, and the flow rate is too small, it is easy to maintain more microporous structures, thereby increasing the microporosity, which will make P1 too high, resulting in m>4000, resulting in too low pore volume and too low capacity of porous silicon-carbon materials; too low activation temperature, too short activation time, too low rotation speed, and too small flow rate are easy to lead to insufficient activation, and failure to fully form a pore structure conducive to lithium ion storage, which will result in N<1nm, too low pore volume, and too low capacity of porous silicon-carbon. From the comparison between Example 1 and Comparative Example 4, it can be seen that if the activation temperature and activation time are too low, the microporosity will be too high, the N value will be too low, and the capacity of porous silicon-carbon will be too low. From the comparison between Example 1 and Comparative Example 5, it can be seen that if the rotation speed and flow rate during the activation process are too low, the microporosity will be too high, the N value will be too low, and the capacity of porous silicon-carbon will be too low.

[0171] It can be seen that under suitable activation conditions, the activation temperature is 700-900°C, the activation time is 1-4h, the rotation speed is 10-40Hz, and the flow rate is 0.5-4L / min, and a porous silicon-carbon material with better electrical properties can be obtained. And by adjusting the above activation conditions, the P1, P2, P3, m, and N values ​​can be adjusted to be within a suitable range, thereby improving the comprehensive electrical properties of the porous silicon-carbon material.

[0172] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A method for preparing porous silicon carbon, characterized in that: The steps include: (1) steam-activating the carbonized product to form an activated product; (2) depositing silicon raw material into the porous structure of the activated product by vapor deposition to produce porous silicon carbon; The indices of the carbonized product and the activated product satisfy the following relationship: In the formula, in, D00, D100, D10, D50, and D90 are the particle size values ​​corresponding to the particle size distribution curve of the carbonized product when the cumulative distribution reaches 0.1%, 100%, 10%, 50%, and 90% respectively; P1, P2, and P3 are the microporosity, mesoporosity, and macroporosity of the activated product, respectively; N is the average pore size of the activated product.

2. The preparation method according to claim 1, characterized in that: The M value is 19-30.

3. The preparation method according to claim 1, characterized in that: The D10, D50 and D90 of the carbonized product satisfy the following relationship: And / or, D00≥2um, D100≤25um.

4. The preparation method according to claim 1, characterized in that: The microporosity P1, mesoporosity P2, and macroporosity P3 of the activated product satisfy the following relationship: Preferably, m=2300-3500.

5. The preparation method according to claim 1, characterized in that: The average pore size N of the activated product is 1-2 nm.

6. The preparation method according to claim 1, characterized in that: The steam activation temperature is 700-900°C and the activation time is 1-4h; And / or, using steam for activation in a rotary kiln with a rotation speed of 10 to 40 Hz and a flow rate of 0.5 to 4 L / min.

7. The preparation method according to claim 1, characterized in that: Obtaining the carbonized product by carbonizing the raw material; Preferably, the raw material is a biomass raw material or a resin-based raw material; Preferably, the biomass raw material is one or more of coconut shell, straw, rice husk, wood, bamboo, bagasse, nut shell, and animal bone marrow; Preferably, the resin-based raw material is one or more of phenolic resin, epoxy resin, and urea-formaldehyde resin; Preferably, the carbonization temperature is 600-1000°C and the carbonization time is 4-10h; Preferably, the carbonizing gas is nitrogen; Preferably, the vapor deposition method is specifically as follows: depositing the activated product and the silicon raw material in a mass ratio of (1-10): (1-2), heating to 400-600°C at a heating rate of 2-20°C / min, keeping the temperature for 1-4h, then heating to 450-650°C at a step temperature gradient of 1-5°C, keeping the temperature for 1-4h, during which the rotary kiln speed is maintained at 10-40Hz, to obtain CVD-coated porous silicon carbon; Preferably, the silicon raw material is one or more of silane, disilane, and dichlorosilane gases.

8. A porous silicon carbon, characterized in that: Porous silicon carbon prepared by the method for preparing porous silicon carbon according to any one of claims 1 to 7.

9. A composite pole piece, characterized in that: The porous silicon carbon comprises the porous silicon carbon as claimed in claim 8, or the porous silicon carbon prepared by any method of claims 1 to 7.

10. A secondary battery, characterized in that: The porous silicon carbon comprises the porous silicon carbon as claimed in claim 8, or the porous silicon carbon prepared by any method of claims 1 to 7.